Analysis of the Development of Learning Models in Geography at Parulian 2 Private High School, Medan - Rosa Delima Lumbantungkup; Widya Asmara; Vivina Marpaung (Jurnal Multidisiplin Sahombu, 2024)
This research analyze the application of innovative learning models in geography subject at Parulian 2 Private High School Medan, focusing on Inquiry Based Learning (IBL) and Project- Based Learning ( PjBL ) models . The results showed that both models were able to increase student engagement , with around 85% of students actively participating in the learning process . However , the implementation faces various challenges , such US limited facilities , teacher readiness , and limited learning time . Based on these findings , the research recommend improving facilities and teacher training to maximize the effectiveness of innovative learning models , US well US flexibility in choosing models that suits the needs of the materials .